Two heterometallic coordination polymers based on Sr(II) ion and dicarboxylate ligand. (1st February 2019) - Chen, Yanmei; Zou, Shuixiang; Tang, Yumeng; Hu, Hailiang
Graphical abstract: Treatment of pyridine-2, 4-dicarboxylate/imidazole with Sr(II) and Zn(II)/Cd(II) under solvothermal conditions gives two 3D coordination polymers. Topological analyses show that1 and2 have structures withpts andqtz topologies, respectively. The solid state luminescent properties of1 and2 were studied. Abstract: Two new heterometallic coordination polymers(CPs) [ZnSr(pydc)2 (H2 O)6 ]n ·2nH2 O (1 ) and [CdSr(pydc)2 (H2 O)2 ]n (2 ) (H2 pydc = pyridine-2, 4-dicarboxylic acid) based on Sr II ion and pyridine-2, 4-dicarboxylate (H2 pydc) have been solvothermally synthesized and characterized. Single crystal structure analysis shows that complex1 is apts topology based on Sr–Zn, and complex2 isqtz topology based on Sr–Cd. Complex2 was the first reported Sr–Cd complex being supported by pyridine-2, 4-dicarboxylic acid. The solid state luminescent properties of1 and2 were studied.